Rollover risk and the maturity transformation function of banks - Teodora Paligorova; Jo\~ao A. C. Santos (Bank of Canada, 2014)
This paper shows that banks that rely heavily on short-term funding engage less in maturity transformation in an attempt to decrease their exposure to rollover risk. These banks shorten both the maturity of their portfolio of loans as well as the maturity of newly issued loans. We find that the loan yield curve becomes steeper with banks' increasing use of short-term funding. The loan maturity shortening is driven by banks and affects borrowers' financing choices - they turn to the bond market for long-term funding. To the extent that borrowers do not manage to compensate for the undesirable shortening of loan maturities by going to the bond market, they may become more exposed to rollover risk due to banks. This potential synchronization of banks' and borrowers' rollover risk can be a source of financial instability once short-term funding suddenly disappears.
Keywords: G21; 330; Financial stability